Ekstraksi Daun Cocor Bebek Menggunakan Berbagai Pelarut Organik Sebagai Inhibitor Korosi Pada Lingkungan Asam Klorida - Tri Reksa Saputra; Agustinus Ngatin (Jurnal Kimia Fullerene, 2019)
Research has been conducted on the extraction of cocor bebek leaves using organic solvents with various levels of solvent polarity. This is done to obtain which solvent has a corrosion inhibitor activity in the hydrochloric acid environment, where five fractions are obtained, namely n-hexane, ethyl acetate, acetone, acetic acid, and methanol. Based on quantitative analysis of cocor bebek leaf extract in variations in the polarity of solvents using a spectrophotometer with a wavelength of 511nm. The flavonoid content in cocor bebek leaf extract produced using acetone solvent showed the highest yield. Corrosion rate of carbon steel in 0.1M HCl solution; 0.05M; 0.01M with the addition of cocor bebek leaf extract decreased as the concentration of extract increased and reached the lowest decrease in the addition of extracts in acetone solvent around 200 ppm with a corrosion rate of 42.18 mpy in 0.1M HCl solution and at an increase in extract concentration there was a decrease does not show a significant reduction in corrosion rate. For 0.05M HCl solution and 0.01m concentration showed a decrease in corrosion rate until the addition of 1500 ppm extract. The results of the extract using acetone solvent showed the corrosion rate of carbon steel in 0.1M HCl solution; 0.05M; and 0.01M lower than the extract results with other solvents (ethyl acetate, methanol, and 5% acetic acid).